2006
DOI: 10.1007/s10495-006-5540-1
|View full text |Cite
|
Sign up to set email alerts
|

Beta-amyloid peptides induces neuronal apoptosis via a mechanism independent of unfolded protein responses

Abstract: Accumulation of beta-amyloid (Abeta) peptides in senile plaques is one of the pathological hallmarks in Alzheimer's disease (AD), which can trigger apoptosis. We have previously demonstrated that Abeta triggered calcium release from the ER. Depletion of ER Ca(2+) ions has been reported leading to unfolded protein responses (UPR). While hypothesis has been made about UPR and neurodegeneration in AD, little is known about the effects of extracellular accumulation of Abeta on UPR. We have shown previously that ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 73 publications
(162 reference statements)
2
35
0
Order By: Relevance
“…Preliminary studies suggested that cultured neurons pre-treated with Fructus lycii extract could attenuate Aß-induced apoptosis via the [25][26][27][28][29][30][31][32][33][34][35] peptide. Neurons were pretreated with LBP-III (10, 100 and 500 μg/ml) for 1 h, followed by a 4-h exposure to 25 μM of Aß [25][26][27][28][29][30][31][32][33][34][35] . Immunoblotting was performed to determine the level of phosphorylated PKR (Thr446/451), total PKR and ß-actin (used as the internal control).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Preliminary studies suggested that cultured neurons pre-treated with Fructus lycii extract could attenuate Aß-induced apoptosis via the [25][26][27][28][29][30][31][32][33][34][35] peptide. Neurons were pretreated with LBP-III (10, 100 and 500 μg/ml) for 1 h, followed by a 4-h exposure to 25 μM of Aß [25][26][27][28][29][30][31][32][33][34][35] . Immunoblotting was performed to determine the level of phosphorylated PKR (Thr446/451), total PKR and ß-actin (used as the internal control).…”
Section: Discussionmentioning
confidence: 99%
“…Primary neuronal cultures were prepared from day 17 embryonic Sprague-Drawley rats (Laboratory Animal Unit, The University of Hong Kong) according to our methods (6,19,20,(23)(24)(25)(26)(27)(28). Briefly, after removal of the meninges the cortices were minced and plated onto poly-L-lysine-(25 μg/ml) coated 6-well plates at 2x10 6 cells/well.…”
Section: Preparation Of Lbp and Separation Of Lbp-iiimentioning
confidence: 99%
See 2 more Smart Citations
“…Amyloid precursor peptides including the toxic Aß 1-42 fragment have previously been shown to induce apoptosis in a variety of cells such as neurons [1][2][3][4][5][6], pancreatic islet cells [7,8], endothelial cells [9] and neutrophils [10]. Mechanisms implicated in amyloid 176 induced apoptosis include Ca 2+ entry [10], calpain activation [5], oxidative stress [1,2,4] and ceramide formation [3].…”
Section: Introductionmentioning
confidence: 99%